Skeletal age and the relationship to midpalatal suture maturation sages : a retrospective radiographic study in a portuguese population - Faerovig, Joaquim Johan Fernandes (2024)
Objectives: The primary aim of this study was to evaluate the degree of correlation between chronological age (CA), cervical vertebrae maturation (CVM) and midpalatal suture maturation (MPSM) in a Portuguese population. A secondary objective was to evaluate the CVM method as a predictive indicator in estimating the degree of MPSM. Materials and Methods: Thirty-three lateral cephalograms and cone beam computed tomography (CBCT) scans from patients aged 9-29 years (20 females and 13 males) were analysed. The CVM stages were assessed on the lateral cephalograms and classified according to the modified method of Baccetti et al. (CVS1 - CVS6). The MPSM stages were evaluated on CBCTs according to Angelieri et al.’s classification system (Stages A - E). Spearman’s rank correlation order and diagnostic performance test were applied to the dataset, with the significance level at p<0.05. Results: A poor correlation was found between CA and stages of MPS. A positive but moderate correlation was observed between CA and CVM, considering both sexes (r=0.625, p<0.001), although stronger in males (r=0.872, p<0.001) compared to females (r=0.463, p=0.040). A moderate correlation was observed between CVM and MPS for the total sample (r=0.433, p=0.012) and males (r=0.603, p=0.029). The diagnostic performance test indicated that only in the case of CVS5 and CVS6 for the assessment of MPS stages D and E, a positive likelihood ratio (LHR) value greater than 10 was observed, indicating a high and often conclusive increase in the likelihood that the CVM corresponds to a specific maturational stage of the MPS. Conclusion: CA is not a good indicator of the MPSM stage among adolescents and young adults. The CVM